Editorial for the Special Collection: Remediation of Learning - Åkerfeldt, Anna; Insulander, Eva; Knutsson, Ola (Designs for Learning, 2023)
This special collection contains articles from participants in the 7th International Designs for Learning Conference - Remediation of Learning. The focus of the conference and the special collection is on current changes in the designs of information and knowledge representations and their consequences on how we understand and evaluate learning and communication. The conference was held in May 2021 and due to the pandemic it was run digitally through Zoom. A total of 43 abstracts were submitted, and all delegates were invited to submit a full paper to the Designs for Learning Journal. Five articles were finally included in the special collection and are presented below, along with an acknowledgement of the abstracts presented during the conference. Keywords: design, education, learning, remediation, designs for learning